Verification and refinement of the System of Rice Intensification (SRI): 1st year trial monitoring report of BRAC sub-project areas - Husain, A.M. Muazzam; Barua, Proloy; Halder, Shantana R (BRAC Research and Evaluation Division (RED), 2020)
We conducted SRI trial in two Upazilas of Noakhali district. The farmers practiced both SRI and conventional cultivation at a time to compare the results regarding production cost, yield and net return. Farmers applied less chemical fertilizers in SRI plots compared to conventional plots, which is expected. They did not use pesticides but adopted IPM cultural method for both practices indicating no attack of pests. Per hectare irrigation cost was more or less same for both practices though it was supposed to be less for SRI method. Water supplier might have counted frequency instead of water volume or there might have been system loss of water in SRI plots. SRI farmers drastically saved seed cost (67%) compared to conventional farmers. Famers weeded their conventional plot by hand while they used hand and also could use the rotary weeder for SRI plot due to wider spacing. It permitted soil aeration, better root development, more effective tiller and more panicle, which ultimately increase the yield in SRI method. During the last Boro season (2002-03) SRI farmers got 43% more yield than conventional one. Yield of straw was 39% higher in SRI compare to traditional method. Per hectare production cost in SRI was 9% less than conventional method. So higher yield and lower cost of production in SRI increased their net return to around 103% over that of traditional practice. Benefit - cost ratio was 2.87 and 1.84 for SRl and conventional method respectively.